21.1k views
3 votes
Lim 1 - cos 40
x>01 - cos 60​

User NMathur
by
4.9k points

1 Answer

5 votes

Answer:

The answer is 4/9 if the problem is:


\lim_(\theta \rightarrow 0)(1-\cos(4\theta))/(1-\cos(6\theta)).

Explanation:

I think this says:


\lim_(\theta \rightarrow 0)(1-\cos(4\theta))/(1-\cos(6\theta)).

Please correct me if I'm wrong about the problem.

Here are some useful limits we might use:


\lim_(u \rightarrow 0)(\sin(u))/(u)=1


\limg_(u \rightarrow 0)(\cos(u)-1)/(u)=0

So for our limit... I'm going to multiply top and bottom by the conjugate of the bottom; that is I'm going to multiply top and bottom by
1+\cos(6\theta):


\lim_(\theta \rightarrow 0)(1-\cos(4\theta))/(1-\cos(6\theta))\cdot(1+\cos(6\theta))/(1+\cos(6\theta))

When you multiply conjugates you only have to do first and last of FOIL:


\lim_(\theta \rightarrow 0)((1-\cos(4\theta))(1+\cos(6\theta)))/(1-\cos^2(6\theta))

By the Pythagorean Identities, the denominator is equal to
\sin^2(6\theta):


\lim_(\theta \rightarrow 0)((1-\cos(4\theta))(1+\cos(6\theta)))/(\sin^2(6\theta))

I'm going to divide top and bottom by
36\theta^2 in hopes to use the useful limits I mentioned:


\lim_(\theta \rightarrow 0)(((1-\cos(4\theta))(1+\cos(6\theta)))/(36\theta^2))/((\sin^2(6\theta))/(36\theta^2))

Let's tweak our useful limits I mentioned so it is more clear what I'm going to do in the following steps:


\lim_(\theta \rightarrow 0)(\sin(6\theta))/(6\theta)=1


\lim_(\theta \rightarrow 0)(\cos(4\theta)-1)/(4\theta)=0

The bottom goes to 1. The limit will go to whatever the top equals if the top limit exists.

So let's look at the top in hopes it goes to a number:


\lim_(\theta \rightarrow 0)(1-\cos(4\theta))/(36\theta^2) \cdot (1+\cos(6\theta)}

We are going to multiple the first factor by the conjugate of the top; that is we are multiply top and bottom by
1+\cos(4\theta):


\lim_(\theta \rightarrow 0)(1-\cos(4\theta))/(36\theta^2) \cdot (1+\cos(4\theta))/(1+\cos(4\theta)) \cdot (1+\cos(6\theta)}

Recall the thing I said about multiplying conjugates:


\lim_(\theta \rightarrow 0)(1-\cos^2(4\theta))/(36\theta^2) \cdot (1+\cos(6\theta))/(1+\cos(4\theta))

We are going to apply the Pythagorean Identities here:


\lim_(\theta \rightarrow 0)(\sin^2(4\theta))/(36\theta^2) \cdot (1+\cos(6\theta))/(1+\cos(4\theta))


\lim_(\theta \rightarrow 0)(\sin^2(4\theta))/((9)/(4)(4\theta)^2) \cdot (1+\cos(6\theta))/(1+\cos(4\theta))


\lim_(\theta \rightarrow 0)(4)/(9)(\sin^2(4\theta))/((4\theta)^2) \cdot (1+\cos(6\theta))/(1+\cos(4\theta))

Ok this looks good, we are going to apply the useful limits I mentioned along with substitution to find the remaining limits:


(4)/(9)(1)^2 (1+\cos(6(0)))/(1+\cos(4(0)))


(4)/(9)(1)(1+1)/(1+1)


(4)/(9)(1)(2)/(2)


(4)/(9)(1)


(4)/(9)

The limit is 4/9.

User Steve Brush
by
5.6k points